2016
DOI: 10.1186/s11671-016-1531-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Crystal Structural Control of Sputtered TiO2 Thin Films

Abstract: In this study, we focused on the origin on the selective deposition of rutile and anatase TiO 2 thin films during the sputtering process. The observation on microstructural evolution of the TiO 2 films by transmission electron microscopy revealed the coexistence of rutile and anatase TiO 2 phases in the initial stage under the preferential growth conditions for the anatase TiO 2 ; the observations further revealed that the anatase phase gradually dominated the crystal structure with increasing film thickness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Although having nanotubes on silicon reduces the reflectance of the surface, particularly in the UV, comparison between the performance of carbon nanotube–silicon solar cells with and without AR layers or strategies shows that these can increase J SC by around 30–40%. Some AR methods employed in carbon nanotube–silicon cells have included encapsulation by polymers such as PMMA, PDMS, or PS, spin‐coating TiO 2 nanoparticles, atomic layer deposited (ALD) MoO x , or silicon surface texturing to form nanowires ( Figure 17 , left), or random pyramids (Figure , right). Some of these methods operate predominantly as scattering layers (e.g., TiO 2 nanoparticles and silicon nanowires/pyramids), some provide improved refractive index matching (e.g., PMMA, PDMS, and PS), others work via constructive interference effects (e.g., MoO x ), and several exploit more than one of these mechanisms.…”
Section: Improving Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Although having nanotubes on silicon reduces the reflectance of the surface, particularly in the UV, comparison between the performance of carbon nanotube–silicon solar cells with and without AR layers or strategies shows that these can increase J SC by around 30–40%. Some AR methods employed in carbon nanotube–silicon cells have included encapsulation by polymers such as PMMA, PDMS, or PS, spin‐coating TiO 2 nanoparticles, atomic layer deposited (ALD) MoO x , or silicon surface texturing to form nanowires ( Figure 17 , left), or random pyramids (Figure , right). Some of these methods operate predominantly as scattering layers (e.g., TiO 2 nanoparticles and silicon nanowires/pyramids), some provide improved refractive index matching (e.g., PMMA, PDMS, and PS), others work via constructive interference effects (e.g., MoO x ), and several exploit more than one of these mechanisms.…”
Section: Improving Performancementioning
confidence: 99%
“…Before our 2012 report on the early progress in this field, and the recent efficiency and active area records, the first report of carbon nanotube–silicon heterojunctions being used specifically for solar cells was by Wei et al in 2007 . The overall power conversion efficiency (PCE) of Wei et al's device was around 1.3% but, as can be seen in Figure 1 and in Table S1 of the Supporting Information, very rapid efficiency gains have been made since then, as might be expected for an architecture based on the already mature field of silicon photovoltaics (PV). However, there is still significant room for improvement in the maximum efficiency of proof‐of‐principle laboratory cells.…”
Section: Introductionmentioning
confidence: 97%
“…The rutile form is more expensive than anatase and is commonly utilized as a coating material, while anatase is used as a photocatalyst material due to its semiconducting properties. [ 172 ] Based on the smaller CV peak separation and higher peak current densities and lower charge‐transfer resistance measured from EIS analysis for anatase compared to that of rutile and an unmodified GF electrode, Cheng et al [ 116 ] concluded that anatase has higher electrocatalytic activity toward the V(II)/V(III) redox reaction. Consequently, they evaluated an anatase TiO 2 ‐GF negative electrode in a VRFB, but its performance was only compared to that of a cell with unmodified graphite felt electrode.…”
Section: All‐vanadium Rfbmentioning
confidence: 99%
“…Extensive investigations show that the HIT-nanowire-based solar cells is a low-cost process for solar cell preparation resulting in a considerable efficiency [242,[292][293][294][295]. The carbon nanotube membranes is introduced as wrapping layer to substitute a-Si:H [296]. Guobin Jia et al proposed a novel multiple core-shell TCO/Al2O3/a-Si:H (p + + i)/c-SiNW structure as shown in Fig.…”
Section: Hybrid Sinw Solar Cellsmentioning
confidence: 99%